The key to quality is good communication: Patients autonomy rights, emotional distress, and trust within healthcare - Vilhjálmsdóttir, Ragnhildur Alda María; Hermannsdóttir, Auður (Stjórnsýslustofnun, 2022)
Patients’ trust in healthcare workers and institutions is the bedrock of quality healthcare services. Trust implies that the patient believes that his interests will be cared for, and his vulnerability will not be exploited. Generally, patients‘ expect their autonomy to be respected, assuming they are empowered to make decisions regarding their treatment. However, studies have shown that nonadherence to patients’ autonomy rights are quite common within healthcare service. The purpose of the study was to shed light on trust towards healthcare service by exploring whether nonadherence to patients’ autonomy rights is likely to diminish patients’ trust. To demarcate the study, the focus was on female patients’ experiences whilst under the care of the Department of Obstetrics and Gynecology at the National University Hospital of Iceland. Prerequisite for participation in the online convenience sample was experience with the service of the Department. The results show that patients with experiences involving incidents of staff ’s nonadherence to patients’ autonomy rights have less trust towards healthcare staff and more distrust towards the hospital than patients who have not experienced such incidents. Moreover, the results show that experiencing emotional distress following an incidence of nonadherence to patient autonomy rights increases distrust towards the hospital. However, the trust that patients have towards doctors, nurses and midwives can curb the development of distrust following an incident. In general, these results underscore the merits of good communication and information exchange with patients, which fosters a feeling that one’s best interests and rights are being upheld. Such communication is likely to promote quality services in healthcare, as well as reduce costs. Traust skjólstæðinga gagnvart heilbrigðisstéttum og heilbrigðisstofnunum er forsenda gæða innan heilbrigðisþjónustu. Traust snýr að tiltrú sjúklings um að hagsmunir hans séu hafðir að leiðarljósi og vanmáttur hans sé ekki misnotaður. ...